Comparing the effects of clear aligners and fixed braces on the quality of life of adolescent patients - LOU Shu, CAI Xiaoyan, ZHANG Chi, ZHANG Yuan, HAN Minxuan, GUAN Zhaolan (Editorial Office of Stomatology, 2024)
Objective To investigate the differences in treatment experience and quality of life between adolescent orthodontic patients using clear aligners and fixed braces. Methods A total of 104 adolescent patients were selected who underwent orthodontic treatment with either clear aligners or fixed braces at Nanjing Medical University Affiliated Stomatological Hospital from January 2022 to June 2022. The patients were divided into two treatment groups based on the type of orthodontic appliance, with 52 patients in each group. Within a 6-month period of using clear aligners or fixed braces, adolescent orthodontic patients were surveyed using the child oral health impact profile-short form 19(COHIP-SF19) and other individual items. The differences in mean satisfaction, quality of life, and statistical scores were compared using independent samples t-tests, while the differences in subjective responses were compared using the Wilcoxon rank-sum test. Results There were no significant differences in mean quality of life and statistical scores between the two groups, but patients in the clear aligner group reported higher satisfaction. The clear aligner group reported greater difficulty with eating, while patients with fixed braces were more likely to experience negative emotions. Additionally, there were no significant differences between the two groups in terms of adaptation time to the appliance, maintaining dental hygiene, and feeling attractive. Conclusion Patients in both groups were generally satisfied with their treatment. Adolescent orthodontic patients treated with clear aligners or fixed braces for at least 6 months exhibit similar overall quality of life.